Mole's hill : a woodland tale - Ehlert, Lois. (San Diego : Harcourt Brace, 1994)
When Fox tells Mole she must move out of her tunnel to make way for a new path, Mole finds an ingenious way to save her home.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
2.2
K-3
Keywords: Woodland Indians -- Folklore; Woodland Indians -- Folklore; Indians of North America -- Legends; Moles (Animals) -- Folklore; Woodland Indians -- Legends; Native Americans -- Folklore -- North America; Moles (Animals) -- Folklore; Woodland Indians -- Legends; Indians of North America -- Legends; Moles (Animals) -- Folklore